How can the heart forget - Loring, Emilie Baker (New York : Grosset & Dunlap, 1960)
Ann Jerome stood on her terrace and stared. Coming toward her was Myles Langdon who had been away for a year. He was her childhood friend and the man she loved. But he was also her sister Sonia's fiance. That hardly surprised Ann-men were taken with her charm and wit but it was Sonia's beauty that really dazzled them Yet Sonia was in love with someone else-